Aluminosilicate glass and method for producing same

By increasing the Cl content in lithium aluminosilicate glass and improving the clarification efficiency of SO3, the problem of residual bubbles and devitrification in the glass is solved, and the full clarification and chemical strengthening performance are improved.

CN119430645APending Publication Date: 2025-02-14AGC INC

Patent Information

Application Number
CN202411458404.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-04-17
Filing Date
2021-04-16
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Lithium-aluminosilicate glass is prone to residual bubbles in the glass and is prone to devitrification when melted, resulting in a decrease in defoaming efficiency or bubbles, making it difficult to achieve sufficient clarification.

Method used

By increasing the Cl content in the glass, the clarification efficiency based on SO3 is improved, and the Cl/(Cl+SO3) content ratio is ensured to be 0.120 or above, and sufficient clarification is achieved.

Benefits of technology

Li-aluminosilicate glass that is fully clarified independent of the coloring components is achieved, and the clarification efficiency and chemical strengthening performance of the glass are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430645A_ABST
    Figure CN119430645A_ABST
Patent Text Reader

Abstract

The invention relates to aluminosilicate glasses and methods of making the same. The present invention relates to an aluminosilicate glass containing 30% or more of SiO2, 10% or more of Al2O3, 2% or more of Li2O, 100 ppm by mass or more of SO3, and 100 ppm by mass or more of Cl, and having a content ratio represented by Cl / (Cl + SO3) of 0.120 or more, as expressed in mass% on the basis of oxides.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with application date of April 16, 2021 and application number 202110411645.4. Technical Field

[0002] The present invention relates to aluminosilicate glass and a method for producing the same. Background Art

[0003] For the protective glass in the display device of mobile devices such as mobile phones, smart phones, portable information terminals (PDAs), and tablet terminals, chemically strengthened glass is used in order to require high strength so that it is not easy to break even when dropped. Various aluminosilicate glasses have been proposed as glasses suitable for chemical strengthening. For example, Patent Document 1 discloses a chemically strengthened glass, wherein the content of each component in the basic composition of the chemically strengthened glass satisfies a specific relationship, the surface compressive stress is 300 MPa or more, the compressive stress value of the part with a depth of 90 μm from the glass surface is 25 MPa or more, and the compressive stress value of the part with a depth of 100 μm from the glass surface is 15 MPa or more.

[0004] For aluminosilicate glass, especially when lithium is contained, ion exchange treatment using a strengthening salt containing sodium and a strengthening salt containing potassium can obtain excellent chemically strengthened glass with large surface compressive stress value (CS) and compressive stress layer depth (DOL).

[0005] As a method for mass production of such glass sheets, the float process is known. When a large amount of glass is produced by the float process, a clarifier is used to reduce bubbles in the glass. For example, in Patent Document 2, sulfates such as sodium sulfate are used as clarifiers.

[0006] Prior art literature

[0007] Patent Literature

[0008] [Patent Document 1] International Publication No. 2017 / 126607

[0009] [Patent Document 2] Japanese Patent Publication No. 48-11325 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, compared with ordinary soda-lime glass, aluminosilicate glass, especially lithium aluminosilicate glass, tends to have bubbles remaining in the glass. This is because the sodium sulfate used as a clarifier is not easy to fully function.

[0012] Furthermore, lithium aluminosilicate glass tends to be easily devitrified during melting, and the devitrification efficiency may be reduced due to the occurrence of devitrification, or devitrification may be easily caused by the generation of bubbles.

[0013] Patent Document 2 describes that the clarification efficiency of sodium sulfate can be improved by controlling the ratio of FeO to Fe2O3 in glass. However, since Fe ions absorb light and cause coloration, this method is difficult to use when the glass is used as a protective glass for a display device.

[0014] Therefore, an object of the present invention is to provide aluminosilicate glass containing lithium which is sufficiently clarified regardless of coloring components, and a method for producing the same.

[0015] Means used to solve problems

[0016] The present inventors have conducted intensive research on the above-mentioned problem and found that even for lithium aluminosilicate glass, the SO3-based clarification efficiency can be improved by increasing the Cl content in the glass.

[0017] That is, the present invention relates to the following [1] to

[10] .

[0018] [1] An aluminosilicate glass, wherein, expressed in terms of mass % based on oxides, the aluminosilicate glass contains more than 30% SiO2, more than 10% Al2O3, more than 2% Li2O, more than 100 mass ppm SO3 and more than 100 mass ppm Cl, and the content ratio represented by Cl / (Cl+SO3) is more than 0.120.

[0019] [2] The aluminosilicate glass as described in [1], wherein, expressed in terms of mass % based on oxides, the aluminosilicate glass contains: 45% to 67% SiO2, 15% to 30% Al2O3, 2% to 8% Li2O, the total content represented by (Li2O+Na2O+K2O) is 3% to 16%, and the total content represented by (MgO+CaO+SrO+BaO) is 0 to 6%.

[0020] [3] The aluminosilicate glass described in [1] or [2], wherein the bubble diameter expansion index I derived by the following calculation method is 0.011 or more: <Calculation method> (i) The glass is melted at a total of three temperatures, namely, 1500°C and two temperatures selected from 1525°C, 1550°C and 1600°C. The diameter D (mm) of bubbles generated in the molten glass is measured every 1 minute from 10 minutes to 30 minutes after melting, and the bubble diameter expansion rate V (mm / hour) is calculated as a value represented by dD / dt for each melting temperature T using the bubble diameter D (mm) and the observation time t (hours). (ii) The value represented by dV / dT obtained from the bubble diameter expansion rate V (mm / hour) at each of the three melting temperatures T (°C) is used as the bubble diameter expansion index I (mm / hour·°C).

[0021] [4] The aluminosilicate glass as described in any one of [1] to [3], wherein the optical basicity of the aluminosilicate glass is 0.546 to 0.570.

[0022] [5] The aluminosilicate glass as described in any one of [1] to [4], wherein the aluminosilicate glass further contains 40 to 300 ppm by mass of Fe2O3, expressed as mass % based on oxide, and has an Fe-redox value of 22% to 60%.

[0023] [6] The aluminosilicate glass as described in any one of [1] to [5], wherein the SnO2 content of the aluminosilicate glass is 100 mass ppm or less.

[0024] [7] The aluminosilicate glass according to any one of [1] to [6], wherein the aluminosilicate glass can be used for chemical strengthening.

[0025] [8] A method for manufacturing aluminosilicate glass, which is a method for manufacturing the aluminosilicate glass described in any one of [1] to [7], wherein the following steps are performed in sequence: heating glass raw materials to obtain molten glass, removing bubbles from the molten glass to clarify it, and shaping the molten glass and slowly cooling it to obtain aluminosilicate glass, and the ratio of SO3 concentration in the aluminosilicate glass to SO3 concentration in the glass raw materials is 0.01 to 0.30.

[0026] [9] A method for manufacturing aluminosilicate glass, which is a method for manufacturing the aluminosilicate glass described in any one of [1] to [7], wherein the following steps are performed in sequence: heating glass raw materials to obtain molten glass, removing bubbles from the molten glass to clarify it, and shaping the molten glass and slowly cooling it to obtain aluminosilicate glass, and the ratio of the Cl concentration in the aluminosilicate glass to the Cl concentration in the glass raw materials is 0.01 to 0.60.

[0027]

[10] The method for producing aluminosilicate glass according to [8] or [9], wherein the minimum viscosity of the molten glass is 10 1.7 dPa·s~10 2.3 dPa·s.

[0028] Effects of the Invention

[0029] According to the present invention, in the lithium aluminosilicate glass that can be used as a chemically strengthened glass useful as a cover glass for a display device, a sufficiently clarified glass can be obtained regardless of the coloring component. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] [ Figure 1 ] Figure 1 Graph showing the relationship between the bubble diameter expansion rate V (mm / hour) and the melting temperature T (° C.) in Examples 1, 3, and 9.

[0031] [ Figure 2 ] Figure 2 Graph showing the relationship between the bubble diameter expansion rate V (mm / hour) and the melting temperature T (° C.) in Examples 2, 10, and 11. DETAILED DESCRIPTION

[0032] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments, and the present invention can be arbitrarily deformed and implemented within the scope of the gist of the present invention. In addition, the " to " indicating a numerical range is used to include the numerical value recorded before and after it as the meaning of the lower limit and the upper limit.

[0033] Unless otherwise specified, the content of each component representing the basic composition of glass is expressed as mass % based on oxides.

[0034] [Aluminosilicate glass]

[0035] The aluminosilicate glass of the present embodiment is lithium aluminosilicate glass (hereinafter, sometimes simply referred to as glass or the present glass).

[0036] Specifically, the aluminosilicate glass is a glass containing 30% or more of SiO2, 10% or more of Al2O3 and 2% or more of Li2O.

[0037] The present glass further contains 100 mass ppm or more of SO 3 and 100 mass ppm or more of Cl, and the content ratio represented by Cl / (Cl+SO 3 ) is 0.120 or more.

[0038] There is no particular limitation on the glass as long as it satisfies the above conditions, but for example, it preferably satisfies the following constitution.

[0039] Expressed as mass % based on oxides, the glass contains: SiO2: 45% to 67%, Al2O3: 15% to 30%, Li2O: 2% to 8%, Li2O+Na2O+K2O: 3% to 16%, and MgO+CaO+SrO+BaO: 0 to 6%.

[0040] Hereinafter, the basic composition of glass will be described.

[0041] SiO 2 is a component constituting the skeleton of glass. In addition, SiO 2 is a component that improves chemical durability and is a component that reduces the generation of cracks when scratches are formed on the glass surface.

[0042] The content of SiO2 is 30% or more, preferably 45% or more, more preferably 50% or more, and further preferably 55% or more. On the other hand, from the viewpoint of improving meltability, the content of SiO2 is preferably 72% or less, more preferably 67% or less, and further preferably 65% ​​or less.

[0043] Al2O3 is a component that increases the Young's modulus of the glass and improves the strength. In addition, when the present glass is a chemically strengthened glass, Al2O3 is an effective component from the viewpoint of improving the ion exchange performance during chemical strengthening and increasing the surface compressive stress after strengthening.

[0044] The content of Al2O3 is 10% or more, preferably 15% or more, more preferably 18% or more, and further preferably 20% or more. On the other hand, from the viewpoint of suppressing the increase of crystal growth rate and the reduction of yield caused by devitrification defects and from the viewpoint of suppressing the increase of viscosity of glass and thus the reduction of meltability, the content of Al2O3 is preferably 30% or less, more preferably 28% or less, and further preferably 22% or less.

[0045] Both SiO2 and Al2O3 are components that increase the melting temperature of glass. Therefore, in order to lower the melting temperature of glass, the total content (SiO2+Al2O3) is preferably 92% or less, more preferably 88% or less, and further preferably 84% or less. In order to stabilize the glass, SiO2+Al2O3 is preferably 65% ​​or more, more preferably 70% or more. In order to further increase the strength, SiO2+Al2O3 is preferably 82% or more.

[0046] Li2O is an essential component of lithium aluminum silicate glass. Li2O is a component that improves the solubility of glass and prevents the glass from being charged. In addition, when the glass is chemically strengthened glass, Li2O is a component that forms surface compressive stress by ion exchange. By containing Li2O in the chemically strengthened glass, it is possible to obtain a stress distribution with large surface compressive stress and compressive stress layer by ion-exchanging Li ions on the glass surface with Na ions and further ion-exchanging Na ions with K ions.

[0047] From the viewpoint of easily obtaining a preferred stress distribution, the content of Li2O is 2% or more, more preferably 3% or more, and further preferably 4% or more.

[0048] The crystal growth rate of lithium aluminosilicate crystals, especially spodumene crystals, is large when the glass is melted, so from the viewpoint of suppressing the reduction in yield caused by devitrification defects, it is preferred to suppress the precipitation of spodumene crystals. Therefore, the content of Li2O is preferably 8% or less, and more preferably 6% or less.

[0049] Na2O and K2O are not essential components, but are components that improve the solubility of glass and reduce the crystal growth rate of lithium silicate glass.

[0050] In order to suppress the devitrification of lithium aluminosilicate glass during melting, the content of Na2O is preferably 0.2% or more, more preferably 2% or more, and further preferably 4% or more. On the other hand, from the viewpoint of improving the strength and weather resistance of the glass, the content of Na2O is preferably 7% or less, and more preferably 5% or less. In order to prevent the charging of lithium aluminosilicate glass, the content of Na2O is preferably 4.8% or less, more preferably 4.5% or less, and further preferably 4.2% or less.

[0051] K2O may be contained for the purpose of suppressing devitrification during melting of glass.

[0052] When K2O is contained, the content of K2O is preferably 0.4% or more, more preferably 0.6% or more, and further preferably 1.2% or more. On the other hand, in order to maintain the weather resistance of the glass, the content of K2O is preferably 4.5% or less, more preferably 3.0% or less, and further preferably 2.0% or less. In order to prevent the lithium aluminum silicate glass from being charged, the content of K2O is preferably 1.9% or less, more preferably 1.8% or less, and further preferably 0.7% or less.

[0053] In order to lower the melting temperature, the total content of alkali metal oxides (Li2O+Na2O+K2O) is preferably 3% or more, more preferably 5% or more, and further preferably 9% or more. On the other hand, in order to maintain the weather resistance of the glass, the total content (Li2O+Na2O+K2O) is preferably 16% or less, and more preferably 14% or less.

[0054] Alkaline earth metal oxides (MgO, CaO, SrO, BaO) are not essential components, but in order to lower the melting temperature while maintaining the stability of the glass, it is preferred to contain any one or more of them. In the case of containing alkaline earth metal oxides, the total content of alkaline earth metal oxides (MgO + CaO + SrO + BaO) is preferably 0.2% or more, more preferably 1% or more, and further preferably 1.5% or more. On the other hand, when the content is too much, the glass becomes unstable, so the total content of alkaline earth metal oxides (MgO + CaO + SrO + BaO) is preferably 6% or less, more preferably 3% or less, and further preferably 1% or less.

[0055] From the viewpoint of increasing the meltability of the glass, MgO may be contained. When MgO is contained, the content of MgO is preferably 0.1% or more, more preferably 1% or more, and further preferably 2% or more. On the other hand, when the content of MgO is too much, the glass becomes unstable, so the content of MgO is preferably 10% or less, and more preferably 5% or less. In the case where the glass is a chemically strengthened glass, from the viewpoint of increasing the compressive stress generated by chemical strengthening, the content of MgO is preferably 3% or less, more preferably 1.5% or less, and further preferably 0.2% or less.

[0056] CaO is a component that improves the meltability of glass, and may be contained. When CaO is contained, the content of CaO is preferably 0.1% or more, and more preferably 0.2% or more. On the other hand, when the content of CaO is too much, the glass becomes unstable, so the content of CaO is preferably 6% or less, and more preferably 4% or less. In the case where the glass is chemically strengthened glass, from the viewpoint of preventing the compressive stress value from being difficult to increase during chemical strengthening treatment, the content of CaO is preferably 0.5% or less, more preferably 0.3% or less, and further preferably 0.1% or less.

[0057] SrO is a component that improves the meltability of glass, and SrO may be contained. When SrO is contained, the content of SrO is preferably 0.1% or more, more preferably 0.2% or more, and further preferably 0.3% or more. On the other hand, when the content of SrO is too much, the glass becomes unstable, so the content of SrO is preferably 6% or less, and more preferably 4% or less. In the case where the glass is a chemically strengthened glass, from the viewpoint of preventing the compressive stress value from being difficult to increase during chemical strengthening treatment, the content of SrO is preferably 0.5% or less, more preferably 0.3% or less, and further preferably 0.1% or less.

[0058] BaO is a component that improves the meltability of glass, and BaO may be contained. When BaO is contained, the content of BaO is preferably 0.1% or more, more preferably 0.2% or more, and further preferably 0.3% or more. On the other hand, when the content of BaO is too much, the glass becomes unstable, so the content of BaO is preferably 6% or less, and more preferably 4% or less. In the case where the glass is a chemically strengthened glass, from the viewpoint of preventing the compressive stress value from being difficult to increase during chemical strengthening treatment, the content of BaO is preferably 0.5% or less, more preferably 0.3% or less, and further preferably 0.1% or less.

[0059] ZnO is a component that improves the meltability of glass, and ZnO may be contained. When ZnO is contained, the content of ZnO is preferably 0.1% or more, more preferably 0.2% or more, and further preferably 0.3% or more. On the other hand, when the content of ZnO is too much, the glass becomes unstable, so the content of ZnO is preferably 10% or less, and more preferably 5% or less. In the case where the glass is a chemically strengthened glass, from the viewpoint of preventing the compressive stress value from being difficult to increase during chemical strengthening treatment, the content of ZnO is preferably 2% or less, more preferably 1.5% or less, and further preferably 0.2% or less.

[0060] Although ZrO2 may not be contained, it is preferably contained in order to improve the strength of the glass. When ZrO2 is contained, the content of ZrO2 is preferably 0.2% or more, more preferably 0.4% or more, and further preferably 1% or more. On the other hand, from the viewpoint of preventing the compressive stress value from being difficult to increase during chemical strengthening treatment, the content of ZrO2 is preferably 4% or less, more preferably 3% or less, and further preferably 1.4% or less.

[0061] Although Y2O3 may not be contained, Y2O3 is a component that improves the strength of the glass. From the viewpoint of suppressing devitrification, it is preferred to contain Y2O3. When Y2O3 is contained, the content of Y2O3 is preferably 1% or more, more preferably 1.5% or more, and further preferably 2% or more. However, when the content of Y2O3 is too much, the glass becomes unstable. Therefore, the content of Y2O3 is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.

[0062] La2O3, Nb2O5, Ta2O5, and Gd2O3 are components that improve the strength of the glass. In order to reduce the crystal growth rate during melting and improve the solubility, La2O3, Nb2O5, Ta2O5, and Gd2O3 may be contained. When these components are contained, the content of each is preferably 1% or more, more preferably 2% or more, and further preferably 3% or more. On the other hand, for the stability of the glass, their total content is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less.

[0063] Although B2O3 is not an essential component, it may be contained for the purpose of reducing the brittleness of the glass, improving the resistance to cracking, and also for the purpose of improving the solubility of the glass. When B2O3 is contained, the content of B2O3 is preferably 0.5% or more, more preferably 1% or more, and further preferably 1.5% or more for the above reasons. On the other hand, from the viewpoint of preventing the acid resistance from deteriorating, the content of B2O3 is preferably 8% or less, more preferably 5% or less, and further preferably 1% or less. From the viewpoint of preventing the generation of ribs (veins) during melting, it is more preferred that substantially no B2O3 is contained.

[0064] P2O5 is not an essential component, but may be contained for purposes such as lowering the melting temperature. When P2O5 is contained, the content of P2O5 is preferably 3% or more, more preferably 5% or more, and further preferably 10% or more. On the other hand, from the viewpoint of improving acid resistance, the content of P2O5 is preferably 16% or less, more preferably 8% or less, and further preferably 4% or less. From the viewpoint of preventing the generation of ribs during melting, it is more preferred that P2O5 is substantially not contained.

[0065] In this specification, glass composed of the above components may be referred to as "basic glass composition".

[0066] Hereinafter, other components that may be contained in the glass in addition to the above-mentioned basic glass composition will be described.

[0067] TiO2 is a component that inhibits the sun exposure of glass, and TiO2 may be contained. When TiO2 is contained, the content of TiO2 is preferably 0.05% by mass or more (500% by mass or more), more preferably 0.1% by mass or more, and further preferably 0.12% by mass or more. On the other hand, from the viewpoint of preventing devitrification and reducing the quality of glass, the content of TiO2 is preferably 0.8% by mass or less, more preferably 0.3% by mass or less, and further preferably 0.15% by mass or less.

[0068] Since Fe2O3 absorbs heat rays, it has the effect of improving the melting property of glass. When a large melting furnace is used to mass produce glass, it is preferred to contain Fe2O3. When Fe2O3 is contained, the content of Fe2O3 is preferably 40 mass ppm or more, more preferably 60 mass ppm or more, and further preferably 80 mass ppm or more. On the other hand, from the viewpoint of preventing coloration of glass and improving transparency, the content of Fe2O3 is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 100 mass ppm or less.

[0069] It should be noted that, although all iron oxides in the glass are described here as Fe2O3, in reality, oxidized Fe(III) and reduced Fe(II) are usually present in a mixture. Among them, Fe(III) produces yellow coloration, Fe(II) produces blue coloration, and the glass produces green coloration under the balance of the two.

[0070] In addition to the above, in the present glass, SO 3 and chloride are used as clarifiers when melting the glass, so that the present glass contains SO 3 and Cl.

[0071] SO 3 is a component that functions as a clarifier, but generally, in the process of manufacturing glass, most of it is decomposed into SO 2 and O 2 and released to the outside of the system in the form of bubbles.

[0072] In order to improve the clarification effect, the content of SO3 is 100 mass ppm or more, preferably 250 mass ppm or more, more preferably 300 mass ppm or more, further preferably 350 mass ppm or more, and particularly preferably 400 mass ppm or more. On the other hand, when the content of SO3 is too high, white bubbles, i.e., sulfate defects, in the glass article increase, and the quality may be reduced. Therefore, the content of SO3 is preferably 2000 mass ppm or less, more preferably 1000 mass ppm or less, further preferably 700 mass ppm or less, and further preferably 600 mass ppm or less.

[0073] As described above, Cl is a component that improves the clarification effect based on SO3 in the present glass, and Cl is an essential component. The content of Cl is 100 mass ppm or more, preferably 150 mass ppm or more, more preferably 200 mass ppm or more, and further preferably 300 mass ppm or more. On the other hand, when the content of Cl is high, the absorption of light caused by Fe(II) ions increases, thereby causing coloration. From this point of view, the content of Cl is preferably 4000 mass ppm or less, more preferably 3000 mass ppm or less, further preferably 2000 mass ppm or less, further preferably 1000 mass ppm or less, further preferably 700 mass ppm or less, and particularly preferably 500 mass ppm or less.

[0074] SnO2 is a component sometimes used as a clarifier for glass, but in the present glass, its content is preferably 100 mass ppm or less, more preferably 50 mass ppm or less, and further preferably 10 mass ppm or less. Thus, when the present glass is formed by a float process, unnecessary coloring can be prevented. In addition, since the present glass contains Cl and SO3, a sufficient clarification effect can be obtained even without adding SnO2.

[0075] As described above, Cl is a component that improves the clarification effect based on SO3 in the present glass, and Cl is an essential component. The ratio of the content of Cl to the total content of Cl and SO3 as clarifiers represented by Cl / (Cl+SO3) is 0.120 or more, more preferably 0.125 or more, and further preferably 0.130 or more. On the other hand, when the content of Cl is too much, the absorption of light by Fe(II) ions increases, thereby causing coloration. From this point of view, the ratio of the content of Cl represented by Cl / (Cl+SO3) is preferably 0.920 or less, more preferably 0.910 or less, and further preferably 0.900 or less.

[0076] Although the glass according to the present embodiment contains lithium, bubbles can be easily removed in the clarification process and high clarification efficiency can be achieved. This is based on the presence of Cl and the effect of SO3, but the clarification efficiency is represented by the bubble diameter expansion index I derived using the following calculation method.

[0077] The cell diameter expansion index I is preferably 0.011 or more, and more preferably 0.012 or more. The upper limit of the cell diameter expansion index I is not particularly limited, but is usually 1.0 or less.

[0078] <Calculation method>

[0079] (i) The glass is melted at a total of three temperatures, namely, 1500° C. and two temperatures selected from 1525° C., 1550° C., and 1600° C. The melting temperature T is set as 0 minute, the diameter D (mm) of bubbles generated in the molten glass is measured every 1 minute, and the bubble diameter expansion rate V (mm / hour) is calculated as a value represented by dD / dt for each melting temperature T using the bubble diameter D (mm) and the observation time t (hour).

[0080] (ii) The value represented by dV / dT obtained from the cell diameter expansion rate V (mm / hour) at each of the three melting temperatures T (° C.) is taken as a cell diameter expansion index I (mm / hour·° C.).

[0081] In the calculation method (i), glass is melted at a melting temperature T, and 50 g of cullet obtained by pulverizing the glass is placed in a quartz cell and melted. For observation of bubbles, HTO (high temperature observation) manufactured by Glass Service can be used.

[0082] The minute immediately after melting was defined as 0 minute, and bubbles in the molten glass were photographed from an observation window using a CCD camera every 1 minute for 10 to 30 minutes, and the bubble diameters were measured by image analysis.

[0083] The above measurement is performed for a total of three melting temperatures, namely 1500°C and two temperatures selected from 1525°C, 1550°C and 1600°C. The slope dD / dt of the approximate straight line when the graph is plotted with the horizontal axis as the observation time t (hours) and the vertical axis as the bubble diameter D (mm) is the bubble diameter expansion rate V (mm / hour) for each melting temperature T.

[0084] In the above calculation method (ii), the horizontal axis is the melting temperature T (°C), and the vertical axis is the bubble diameter expansion rate V (mm / hour) represented by dD / dt obtained in the above (i). The bubble diameter expansion rate V is plotted for each of the three melting temperatures T, and the value represented by the slope dV / dT of the approximate straight line at this time is defined as the bubble diameter expansion index I (mm / hour·°C).

[0085] It should be noted that any of the melting temperatures used in the calculation of the bubble diameter expansion index I is above 1500°C. This is because, depending on the compound serving as a Cl source used as a glass raw material, when the temperature is less than 1500°C, the amount of gasification is small, which does not help improve the clarification efficiency, or even if it helps, the effect is small.

[0086] The optical basicity of glass is a value related to the ease with which SO3 is released to the outside of the system during the clarification process. When the sum of the products of the basicity and the molar percentage of the oxides constituting the glass is large, the optical basicity of the glass is large and SO3 is not easily released.

[0087] Lithium aluminosilicate glass contains Li2O as an alkali metal oxide, but the basicity of Li2O is lower than that of other alkali metal oxides. Therefore, it is estimated that conventional lithium aluminosilicate glass easily releases SO3.

[0088] In contrast, the optical basicity of the glass according to the present embodiment is preferably 0.546 or more, more preferably 0.548 or more. On the other hand, when the basicity is too high, the lithium silicate glass may be easily devitrified during melting, so the optical basicity is preferably 0.570 or less, more preferably 0.560 or less, and even more preferably 0.556 or less.

[0089] Fe-redox value is Fe converted to Fe2O3 2+ The ratio of the content to the total iron content converted to Fe2O3. Therefore, the Fe-redox value is an indicator of the O2 concentration in the glass and indicates the redox state.

[0090] The larger the Fe-redox value, the more degassing can be achieved during clarification, and the more efficiency of clarification by SO3 can be improved. On the other hand, the presence of Fe2O3 may cause coloring of the glass. In contrast, for the glass of this embodiment, the clarification efficiency is improved due to the presence of Cl, so even if the Fe-redox value is lower than before, a good clarification effect can be obtained.

[0091] The Fe-redox value is preferably 22% or more, more preferably 25% or more, and further preferably 28% or more. On the other hand, from the viewpoint of making it easy for light in the near-ultraviolet wavelength region to pass through and improving the solubility of the glass raw material, the Fe-redox value is preferably 60% or less, more preferably 58% or less, and further preferably 55% or less.

[0092] The β-OH value is an indicator of the amount of water in the glass. Glass with a large β-OH value has a lower softening point and tends to be easier to bend. Therefore, when bending, the β-OH value is preferably 0.24 mm. -1 More preferably 0.25 mm -1 More preferably, 0.26 mm -1 On the other hand, from the perspective of improving strength by chemical strengthening of glass, when the β-OH value of glass increases, the value of surface compressive stress (CS) after chemical strengthening treatment decreases, making it difficult to improve strength. Therefore, the β-OH value is preferably 0.37 mm -1Below, more preferably 0.36mm -1 Below, more preferably 0.35 mm -1 Hereinafter, the β-OH value can be increased by, for example, adopting a float process as a method for producing glass.

[0093] The β-OH value was determined by FT-IR with a reference wavelength of 4000 cm -1 The transmittance under X1 (%), the absorption wavelength of hydroxyl group is 3570cm -1 The minimum transmittance X2 (%) near the surface and the thickness t (unit: mm) of the glass plate are calculated according to the following formula.

[0094] β-OH value = (1 / t)log 10 (X1 / X2)

[0095] The β-OH value can be adjusted by the amount of water contained in the glass raw material and the melting conditions.

[0096] When the devitrification temperature of the glass is high, the clarification efficiency is generally reduced. This is because bubbles are generated when the devitrification is eliminated. Since the region where the devitrification occurs becomes wider when the devitrification temperature is high, the generated bubbles also become more, and it is not possible to completely clarify the glass with SO3 alone. However, in the case of the glass of this embodiment, due to the presence of Cl, even if the devitrification temperature becomes high, the generated bubbles can be fully clarified. Therefore, the devitrification temperature of the glass can be higher than before, for example, it can be above 1120°C.

[0097] When the viscosity of the glass is high, it is difficult to remove bubbles. Therefore, in order to obtain the desired clarification effect, it is preferable to increase the temperature of the clarification process. However, high temperature increases damage to the melting furnace and is also costly. In contrast, in the case of the glass of this embodiment, due to the presence of Cl, the bubbles generated can be fully clarified even in a state of high viscosity. Therefore, the viscosity of the glass can be higher than before, for example, the viscosity can reach 10 2 dPa·s when the temperature (T2) can be 1580°C or higher. 4 The temperature (T4) at dPa·s may be 1135° C. or higher.

[0098] The glass according to the present embodiment is preferably used as chemically strengthened glass. That is, the glass is preferably chemically strengthened to form chemically strengthened glass.

[0099] In addition, the glass is particularly useful as a protective glass for display devices such as mobile phones, smart phones, portable information terminals (PDAs), tablet terminals and other mobile devices. In addition, it is also useful as protective glass for display devices such as televisions (TVs), personal computers (PCs), touch panels, etc. that are not intended to be carried, building materials such as elevator walls, walls of buildings such as houses or buildings (full-screen displays), window glass, etc., desktops, interiors of cars or airplanes, etc. or their protective glass, and shells having non-plate-shaped curved surfaces by bending and forming.

[0100] [Method for producing aluminosilicate glass]

[0101] The method for producing aluminosilicate glass according to the present embodiment includes the following steps (i) to (iii) in order.

[0102] (i) a melting step of heating glass raw materials to obtain molten glass,

[0103] (ii) a clarification step of removing bubbles from the molten glass, and

[0104] (iii) A step of shaping and slowly cooling the molten glass to obtain aluminosilicate glass.

[0105] In addition, in the glass raw material in the step (i) and the aluminosilicate glass obtained in the step (iii), the concentration of at least one of SO 3 and Cl satisfies the following condition.

[0106] The ratio of the SO 3 concentration in the aluminosilicate glass obtained in the step (iii) to the SO 3 concentration in the glass raw material in the step (i) is 0.01 to 0.30.

[0107] The ratio of the Cl concentration in the aluminosilicate glass obtained in the step (iii) to the Cl concentration in the glass raw material in the step (i) is 0.01 to 0.60.

[0108] Thus, aluminosilicate glass containing lithium and having an SO 3 content of 100 mass ppm or more and a Cl content of 100 mass ppm or more is obtained.

[0109] (i. Melting process)

[0110] In the melting step of heating glass raw materials to obtain molten glass, the raw materials are adjusted so as to have a desired glass composition, and the raw materials are placed in a melting furnace and heated and melted.

[0111] As glass raw materials, oxides, carbonates, sulfates, nitrates, hydroxides, halides such as chlorides, etc. can be used. By using sulfates, SO3 having a clarifying effect can be contained in the glass, and by using chlorides, Cl can be contained in the glass.

[0112] Glass raw materials are adjusted so that the composition of the obtained glass becomes the composition described in the above-mentioned [aluminosilicate glass].

[0113] The SO3 concentration in the glass raw material needs to be excessive relative to the desired SO3 concentration in the glass composition because, in the subsequent clarification step, SO3 is decomposed into SO2+1 / 2O2 alone in addition to SO3 involved in clarification and discharged out of the system.

[0114] On the other hand, in the production method of the present embodiment, the following effect has been newly found: due to the presence of Cl, clarification is performed together with SO 3 , thereby improving the clarification efficiency.

[0115] Therefore, according to the manufacturing method of this embodiment, the ratio of the SO3 concentration in the aluminosilicate glass to the SO3 concentration in the glass raw material can be achieved in the range of 0.01 to 0.30. This ratio is preferably 0.05 or more, preferably 0.15 or more, and preferably 0.25 or less.

[0116] In the clarification process, since Cl is discharged to the outside of the system like SO3, the Cl concentration in the glass raw material needs to be excessive relative to the Cl concentration in the desired glass composition. Specifically, since the ratio of the Cl concentration in the aluminosilicate glass to the Cl concentration in the glass raw material is 0.01 to 0.60, it is preferable to perform an inverse operation to specify the Cl concentration in the glass raw material. The ratio is preferably 0.02 or more, more preferably 0.05 or more, further preferably 0.1 or more, and further preferably 0.3 or more. In addition, the ratio is preferably 0.55 or less, more preferably 0.50 or less, and further preferably 0.45 or less.

[0117] The minimum viscosity of molten glass refers to the minimum viscosity within the temperature range of melting glass raw materials to form molten glass, and can be adjusted by the heating method, that is, the amount of heavy oil combustion, gas combustion or electric flux used in the melting furnace. From the viewpoint that even if bubbles are generated, the bubbles are easily released to the outside, the minimum viscosity of molten glass is preferably 10 2.3 dPa·s or less, more preferably 10 2.2 dPa·s or less, more preferably 10 2.1In addition, when the viscosity of the molten glass is too low, the flow rate of the molten glass billet becomes faster, and there is insufficient time for initial melting and clarification. The minimum viscosity of the molten glass is preferably 10 1.7 dPa·s or more, more preferably 10 1.8 dPa·s or more, more preferably 10 1.9 dPa·s or above.

[0118] The minimum viscosity of the molten glass can be determined by measuring the billet temperature in the highest temperature range.

[0119] As long as the glass raw material melts, the melting temperature is not particularly limited. From the viewpoint of improving initial solubility, the melting temperature is preferably 1500° C. or higher, more preferably 1550° C. or higher. From the viewpoint of suppressing coloration caused by Fe(II), the melting temperature is preferably 1680° C. or lower, more preferably 1650° C. or lower. The melting temperature does not need to be constant, and the temperature may be changed by, for example, melting at a specific temperature for a certain period of time and then further raising the temperature again to a high temperature.

[0120] The melting time is preferably more than 1 hour, more preferably more than 5 hours, and further preferably more than 10 hours. The upper limit of the melting time is not particularly limited, and from the viewpoint of suppressing the coloring caused by Fe (II), it is preferably less than 30 hours, more preferably less than 25 hours, and further preferably less than 20 hours. In addition, in order to ensure homogeneity after the glass is melted, the molten glass can be stirred for a certain time, and preferably their total time is within the above range.

[0121] In order to obtain high melting efficiency and high-quality glass, the melting process is preferably carried out under an appropriate oxygen active state. Specifically, in order to become the desired oxygen active state, that is, in order to obtain the desired redox reaction, the oxygen concentration in the melting furnace is preferably set to 1.0 volume % or more, more preferably 1.3 volume % or more, and further preferably 1.5 volume % or more. In addition, from the viewpoint of retaining the required SO3 in the clarification process, the oxygen concentration is preferably 10 volume % or less, more preferably 8 volume % or less, and further preferably 6 volume % or less. For example, the oxygen concentration can be controlled by the amount of N2 gas, O2 gas, or air blown in.

[0122] (ii. Clarification process)

[0123] The clarification step is a step of removing bubbles from the molten glass obtained in the above-mentioned melting step. In the clarification step, a degassing method using reduced pressure can be used.

[0124] SO3 and Cl were used as clarifiers.

[0125] As the SO3 source, a sulfate of at least one element selected from the group consisting of Li, Na, K, Al, Mg and Ca is preferred, among which Na2SO4 acts as a silica sand melting accelerator, and Na2SO4 is further preferred from the viewpoint of reducing initial bubbles and being inexpensive and readily available.

[0126] As the Cl source, a chloride of at least one element selected from the group consisting of Li, Na, K, Al, Mg and Ca is preferred, and NaCl and KCl are more preferred from the viewpoints that they have a boiling point at the temperature of the clarification region of the melting tank, have low deliquescent properties, and are inexpensive and readily available.

[0127] Even if the bubble diameter expansion index I of the obtained glass is 0.011 or more, the clarification efficiency of the clarification process in the present embodiment is high. Therefore, even in a short time, good degassing can be performed. The retention time in the clarification process is preferably 1 hour or more, more preferably 3 hours or more, and more preferably 5 hours or more. In addition, from the viewpoint of suppressing the coloring caused by Fe (II), the retention time is preferably 50 hours or less, more preferably 45 hours or less, and more preferably 40 hours or less.

[0128] The temperature in the clarification process is preferably a temperature at which the compound serving as a Cl source enters the bubbles in the form of gas. For example, when NaCl is used as a Cl source, NaCl reaches 1 bar at about 1465°C and enters the bubbles in the form of NaCl gas, thereby promoting clarification. That is, by forming such a state, the clarification efficiency can be improved by the presence of Cl.

[0129] The temperature in the clarification step varies depending on the type of compound used as the Cl source, but is, for example, preferably 1465°C or higher, more preferably 1525°C or higher, further preferably 1550°C or higher, and is preferably 1680°C or lower, more preferably 1650°C or lower.

[0130] In order to achieve high clarification efficiency, it is also preferred to set an appropriate oxygen activity state in the clarification process. Therefore, the oxygen concentration in the furnace in the clarification process is preferably 1.0 volume % or more, more preferably 1.3 volume % or more, and further preferably 1.5 volume % or more. In addition, the oxygen concentration is preferably 15 volume % or less, more preferably 13 volume % or less, and further preferably 10 volume % or less. For example, the oxygen concentration can be controlled by the amount of N2 gas, O2 gas, or air blown in.

[0131] (iii. Forming and slow cooling process)

[0132] The shaping and slow cooling step is a step of shaping the molten glass from which bubbles have been removed in the clarification step and slowly cooling it to obtain aluminosilicate glass.

[0133] The glass forming method is not particularly limited, and examples thereof include the float process, the pressing process, the fusion process, and the down-draw process. The float process, which is suitable for mass production, is particularly preferred. In addition, continuous forming methods other than the float process, such as the fusion process and the down-draw process, are also preferred.

[0134] The slow cooling step is a step of slowly cooling the molten glass or formed glass to room temperature. The slow cooling step is not particularly limited, and examples thereof include a method of slowly cooling to room temperature at a cooling rate of 10°C / min to 200°C / min.

[0135] The glass after forming and slow cooling can be ground or polished as needed. In addition, the glass can be cut into a specified shape and size, or chamfered.

[0136] When the glass is used as a cover glass for a display device, it is preferably further subjected to a strengthening treatment such as a chemical strengthening treatment or a physical strengthening treatment, and more preferably subjected to a chemical strengthening treatment to obtain a chemically strengthened glass. The strengthening treatment may be carried out by a conventionally known method.

[0137] The chemical strengthening treatment is an ion exchange treatment, which can be performed, for example, by immersing the glass in a molten salt heated to 360° C. to 600° C. for 0.1 to 500 hours. It should be noted that the heating temperature of the molten salt is preferably 375° C. to 500° C., and the immersion time of the glass in the molten salt is preferably 0.3 to 200 hours.

[0138] As the molten salt for chemical strengthening treatment, nitrates, sulfates, carbonates, chlorides, etc. can be listed. Among them, as nitrates, lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, silver nitrate, etc. can be listed. As sulfates, lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, silver sulfate, etc. can be listed. As carbonates, lithium carbonate, sodium carbonate, potassium carbonate, etc. can be listed. As chlorides, lithium chloride, sodium chloride, potassium chloride, cesium chloride, silver chloride, etc. can be listed. These molten salts can be used alone or in combination.

[0139] The treatment conditions of the chemical strengthening treatment are not particularly limited, and appropriate conditions can be selected in consideration of the properties and composition of the glass, the type of molten salt, and the chemical strengthening properties such as the surface compressive stress and the depth of the compressive stress layer desired for the final chemically strengthened glass.

[0140] [Example]

[0141] Hereinafter, the present invention will be specifically described with reference to test examples, but the present invention is not limited to these test examples.

[0142] [Example 1 to Example 11]

[0143] The raw materials were mixed to form the raw material composition shown in Table 1. The total of the components in Table 1 does not strictly reach 100% by mass because the glass basic composition is expressed in mass %, while other components are expressed in mass ppm, and there is a difference in their significant figures.

[0144]

[0145] The prepared glass raw material mixture is placed in a platinum crucible. Then, the platinum crucible is placed in an electric furnace at 1500°C and kept for 2 hours to melt the glass raw materials. In addition, the electric furnace is heated again, and the molten glass is stirred for 1 hour at a temperature range of 1600°C to 1650°C using a platinum stirrer to ensure homogeneity. The oxygen concentration range at this time is adjusted by N2 gas to be 1% by volume to 3% by volume (melting process).

[0146] Next, the platinum stirrer used for stirring was withdrawn, and the temperature range was controlled to be 1600° C. to 1650° C. and the oxygen concentration was controlled to be in the range of 1 vol % to 3 vol % to carry out clarification (clarification step) by maintaining the mixture for 1 hour.

[0147] The clarified glass was poured into the mold material, kept at 640°C for 1 hour, and then cooled to 520°C at a rate of 1°C / min. Then, it was kept at 520°C for 2 hours and cooled to room temperature at a rate of 10°C / min to obtain a glass block (forming and slow cooling process).

[0148] The obtained glass block was crushed to obtain aluminosilicate glass cullets.

[0149] It should be noted that, as glass raw materials, Na2SO4 sulfate was used as an SO3 source, and NaCl chloride was used as a Cl source.

[0150] The obtained glass was crushed using a planetary ball mill, and the obtained powder was pressed into a granular form and measured for X-ray fluorescence, and quantitative analysis was performed using the fundamental parameter method (FP method). For chlorine, in order to improve the measurement accuracy, quantitative analysis was performed using the calibration curve method. The results are recorded in Table 2, Examples 1 and 2 are comparative examples, and Examples 3 to 11 are examples.

[0151] The total of the components in Table 2 does not strictly reach 100 mass % because the content of the component is expressed in mass % and mass ppm and there is a difference in the significant figures therebetween.

[0152] In addition, although Example 10 and Example 11 in Table 1 have the same composition, the melting temperatures are made different by setting them to 1650° C. in Example 10 and 1610° C. in Example 11, resulting in the difference between Example 10 and Example 11 in Table 2.

[0153] In Table 2, "SO3(glass) / SO3(raw material)" represents the ratio of the SO3 concentration (mass ppm) in the obtained aluminosilicate glass to the SO3 concentration (mass ppm) in the glass raw material. Similarly, "Cl(glass) / Cl(raw material)" represents the ratio of the Cl concentration (mass ppm) in the obtained aluminosilicate glass to the Cl concentration (mass ppm) in the glass raw material. "Cl(glass) / (Cl(glass)+SO3(glass))" represents the ratio of the Cl content in the obtained aluminosilicate glass to the total content of Cl and SO3.

[0154] In addition, the glass raw materials shown in Table 1 do not contain Fe2O3, while the obtained aluminosilicate glass shown in Table 2 contains Fe2O3. This means that Fe2O3 is not intentionally added as a glass raw material, and Fe2O3 is derived from substances contained in the raw materials as impurities. In other words, the Fe2O3 content is not adjusted as the blending composition of the glass raw materials.

[0155]

[0156] [physical properties]

[0157] The Fe-redox value, optical basicity, bubble diameter expansion index I, and β-OH value of the obtained glass were determined by the following methods.

[0158] (Fe-redox)

[0159] A known weight (100 mg to 300 mg) of glass was placed in a polytetrafluoroethylene (PTFE) container and dissolved in a hydrofluoric acid (18% by mass)-hydrochloric acid (25% by mass) aqueous solution under a nitrogen atmosphere. Fe(II) was stabilized with a boric acid aqueous solution (4% by mass), and the resulting solution was transferred to a 100 mL volumetric flask and fixed to volume. This was referred to as solution A.

[0160] In the analysis of Fe(II) concentration, 25 mL was taken from solution A, 2 mL of 2,2'-bipyridine solution (1.0 mass %) was added, and then 8 mL of ammonium acetate aqueous solution (5 mass %) was added to adjust the pH to 4-5 to develop color. This was referred to as solution B. The absorbance of the generated orange-red iron (II) complex was measured by the method described below to quantify the Fe(II) concentration.

[0161] Regarding the total Fe concentration, 25 mL of solution A was taken, and 1 mL of hydroxylamine hydrochloride aqueous solution (0.1 mass %) was added to reduce the iron to Fe(II). Then, 2 mL of 2,2'-bipyridine solution (1.0 mass %) was added, and then 8 mL of ammonium acetate aqueous solution (5 mass %) was added to adjust the pH to 4-5 to develop color. This was referred to as solution C.

[0162] The absorbance of the obtained solution B and solution C at a wavelength of 538 nm was measured by a spectrophotometer (manufactured by JASCO Corporation, UV-visible spectrophotometer, V-750), and the Fe (II) concentration and the total Fe concentration were quantified using a calibration curve. From these results, the Fe-redox value represented by Fe-redox = {[Fe (II) concentration] / [total Fe concentration]} was obtained.

[0163] (Optical Alkalinity)

[0164] The optical basicity of the glass is calculated from the sum of the products of the basicity and the mole percentage of each oxide constituting the glass.

[0165] The basicity of each oxide is shown in Table 3.

[0166]

[0167] (Bubble diameter expansion index I)

[0168] 50 g of the obtained cullet was placed in a quartz cell, and the quartz cell was placed in an electric furnace (manufactured by Glass Service, high temperature observation; HTO) heated to 1500°C to melt the cullet. The diameter D (mm) of the bubbles generated in the molten glass was measured every 1 minute from 10 to 30 minutes, with the diameter D (mm) of the bubbles and the observation time t (hours) being set as 0 minutes immediately after melting. The bubble diameter expansion rate V (mm / hour) represented by dD / dt was calculated. For the observation of the bubbles, a CCD camera was used to take pictures from the observation window provided on the HTO, and the diameter of the bubbles was measured by image analysis.

[0169] Regarding the glasses of Examples 1 and Examples 3 to 9, the melting temperature T was changed from 1500° C. to 1525° C. and 1550° C., and the same operation as above was performed to determine the bubble diameter expansion rate V (mm / hour) at each temperature.

[0170] Regarding the glasses of Examples 2, 10 and 11, the melting temperature T was changed from 1500° C. to 1550° C. and 1600° C., and the same operation as above was performed to determine the bubble diameter expansion rate V (mm / hour) at each temperature.

[0171] A graph is plotted with the cell diameter expansion rate V (mm / hour) obtained above as the vertical axis and the melting temperature T (° C.) as the horizontal axis. Figure 1 , Figure 2 The slope dV / dT of the graph is defined as the bubble diameter expansion index I (mm / hour·°C).

[0172] (β-OH value)

[0173] The reference wavelength was 4000 cm-1 using a Fourier transform infrared spectrometer (Nicolet iS-50 manufactured by Thermo Fisher Scientific). -1 The transmittance X1(%) and the absorption wavelength of hydroxyl group are 3570cm -1 The minimum transmittance near X2 (%) is calculated by using these and the thickness t (mm) of the glass sample according to the following formula.

[0174] β-OH value = (1 / t)log 10 (X1 / X2)

[0175] The glass of the example in which the Cl content increases together with SO3 has a larger bubble diameter expansion index I, and it is considered that when the glass is kept at the same temperature for the same time, the bubble diameter is expanded compared with the glass without Cl. From this result, it can be considered that according to Stoke's law, the floating speed of the bubbles contained in the glass containing SO3 and Cl becomes faster, and it can reach the surface layer in a short time and burst the bubbles.

[0176] Based on the above results, the glass of the example does not need to control the ratio of FeO and Fe2O3 as coloring components, and thus can provide aluminosilicate glass containing lithium that is not colored and is sufficiently clear.

[0177] The above describes the appropriate embodiments of the present invention, but the present invention is not limited to the above embodiments, and various design changes can be made within the scope of the claims. This application is based on Japanese patent application No. 2020-074100 filed on April 17, 2020, the contents of which are incorporated herein by reference.

Claims

1. An aluminosilicate glass, wherein: The aluminosilicate glass comprises, expressed in terms of mass % based on oxides, 30% or more of SiO2, 10% or more of Al2O3, 4% to 6% of Li2O, 100 mass ppm or more and 700 mass ppm or less of SO3, 100 mass ppm or more of Cl, and 40 mass ppm or more of Fe2O3, and The total content of SiO2 and Al2O3 is 70% to 84%, the total content represented by (MgO+CaO+SrO+BaO) is 0.2% to 3%, and the content ratio represented by Cl / (Cl+SO3) is greater than 0.

120.

2. The aluminosilicate glass according to claim 1, wherein: Expressed in terms of mass % on an oxide basis, the aluminosilicate glass contains: 55%~67% SiO2, 15% to 28% Al2O3, The total content represented by (Li2O+Na2O+K2O) is 4% to 16%.

3. The aluminosilicate glass according to claim 1 or 2, wherein: The bubble diameter expansion index I derived by the following calculation method is 0.011 or more, Calculation method: (i) setting the melting temperature T to a total of three temperatures, namely, 1500° C. and two temperatures selected from 1525° C., 1550° C., and 1600° C., and melting the glass; setting the time immediately after melting to 0 minutes and measuring the diameter D of bubbles generated in the molten glass every 1 minute for 10 minutes to 30 minutes, and using the bubble diameter D and observation time t, determining the bubble diameter expansion rate V as a value represented by dD / dt for each melting temperature T, wherein the unit of the bubble diameter D is mm, the unit of the observation time t is hour, and the unit of the bubble diameter expansion rate V is mm / hour, (ii) The value represented by dV / dT obtained from the bubble diameter expansion rate V at each of the three melting temperatures T is taken as the bubble diameter expansion index I, wherein the unit of the melting temperature T is ° C. and the unit of the bubble diameter expansion index I is mm / hour·° C.

4. The aluminosilicate glass according to claim 1 or 2, wherein: The ZnO content of the aluminosilicate glass is 2.0% or less.

5. The aluminosilicate glass according to claim 1 or 2, wherein: The aluminosilicate glass contains 40 to 300 ppm by mass of Fe 2 O 3 , and has a Fe-redox value of 22% to 60%.

6. The aluminosilicate glass according to claim 1 or 2, wherein: The SnO2 content of the aluminosilicate glass is 100 mass ppm or less.

7. The aluminosilicate glass according to claim 1 or 2, wherein: The aluminosilicate glass can be used for chemical strengthening.

8. The aluminosilicate glass according to claim 1 or 2, wherein: The TiO2 content of the aluminosilicate glass is 0.8 mass % or less.

9. The aluminosilicate glass according to claim 1 or 2, wherein: The aluminosilicate glass contains substantially no P2O5.

10. The aluminosilicate glass according to claim 1 or 2, wherein: The aluminosilicate glass contains substantially no B2O3.

11. A method for producing aluminosilicate glass, which is a method for producing the aluminosilicate glass according to any one of claims 1 to 10, wherein: Follow these steps: The glass raw materials are heated to obtain molten glass. removing bubbles from the molten glass to clarify it, and The molten glass is shaped and slowly cooled to obtain aluminosilicate glass, and The ratio of the SO 3 concentration in the aluminosilicate glass to the SO 3 concentration in the glass raw material is 0.01 to 0.

30.

12. A method for producing an aluminosilicate glass, which is a method for producing the aluminosilicate glass according to any one of claims 1 to 10, wherein: Follow these steps: The glass raw materials are heated to obtain molten glass. removing bubbles from the molten glass to clarify it, and The molten glass is shaped and slowly cooled to obtain aluminosilicate glass, and The ratio of the Cl concentration in the aluminosilicate glass to the Cl concentration in the glass raw material is 0.01 to 0.

60.

13. The method for producing aluminosilicate glass according to claim 11 or 12, wherein: The minimum viscosity of the molten glass is 10 1.7 dPa·s~10 2.3 dPa·s.

Citation Information

Patent Citations

  • JP1973011325B1

  • Image processing device, image processing method, and program

    JP2020074100A

  • Chemically strengthened glass, and glass for chemical strengthening

    WO2017126607A1

Cited By

  • Lithium-aluminum-silicon glass suitable for float electric boosting

    CN120058231A